Fuzzy Critical Path Method Using Triangular Bipolar Fuzzy Numbers - Rajeshwari, M.; Murugesan, R.; A. Venkatesh, K. (International Journal of Engineering and Technology, 2018)
The basic issue is a traditional and vital system improvement showing up in numerous applications, particularly in arranging also and controlling the complex projects. Anyway after the effect of traditional basic way strategy calculation can't appropriately coordinate this present reality issue. In this paper, two unique calculations are exhibited to acquire the basic way in a fuzzy system, where the edge weights are taken as triangular bipolar fuzzy numbers and triangular fuzzy numbers separately.Â Â Â